Gabapentin Attenuates Ocular Inflammation: In vitro and In vivo Studies - Anfuso, Carmelina D.; Olivieri, Melania; Fidilio, Annamaria; Lupo, Gabriella; Rusciano, Dario; Pezzino, Salvatore; Gagliano, Caterina; Drago, Filippo; Bucolo, Claudio (Frontiers in Pharmacology, 2017)
To investigate the effects of gabapentin, a structural analogue of γ-amino butyric acid (GABA), on the inflammatory response of lipopolysaccharide (LPS)‑stimulated rabbit corneal cells (SIRC) and on endotoxin-induced uveitis (EIU) in rabbits. We investigated the LPS-induced expression of several inflammatory mediators, such as TNF-α, IL-1β, cPLA2, COX-2 and PGE2 in the SIRC cells with or without gabapentin treatment. Gabapentin treatment significantly (p<0.05) attenuated cytokines production, cPLA2 activation, COX-2 expression and PGE2 levels in SIRC. EIU was induced by an intraocular injection of 0.1 μg of LPS in albino rabbit eye. After 7 and 24 hours from LPS injection clinical signs of ocular inflammation were examined by slit lamp with or without topical treatment of 0.5% gabapentin. Tears, aqueous, cornea, conjunctiva and iris-ciliary body were collected and inflammatory biomarkers assessed. Topical treatment with gabapentin significantly (p<0.05) reduced clinical signs and biomarkers of inflammation compared with the LPS group both at 7 and 24 hours. In conclusion, the results generated in the present study suggest that ophthalmic formulation based on gabapentin may be useful in the treatment of inflammatory conditions associated to ocular pain such as uveitis, and that clinical studies to evaluate this possibility may be warranted.